3D Finite Element Analysis of Knee Joint Stress Distribution Under Muscle Action with Partial ACL Rupture - Pei, Shize (Scientific Journal of Technology, 2025)
This study aimed to investigate the impact of partial rupture of the anterior cruciate ligament (ACL) on the stress distribution within the meniscus and cartilage of the knee joint using finite element analysis. The findings provide a theoretical foundation for the clinical prevention and treatment of ACL injuries. The anteromedial bundle of the ACL is crucial for maintaining valgus stability in the knee during standing with the knee in extension. A reduction in valgus or rotational stability leads to a redistribution of stress within the joint, making the meniscus, as a cushioning structure, more susceptible to injury. Consequently, in sports requiring high knee rotational stability, clinicians should be vigilant for potential secondary meniscal injuries, particularly involving the anteromedial bundle, and consider early clinical intervention to mitigate further damage.